Preparation method of iron-impregnated alternanthera philoxeroides hydrothermal carbon and carbon sequestration application thereof
By immersing hollow lotus seed grass by FeCl3, minerals are converted into FeC2O4, iron-impregnated hollow lotus seed grass hydrothermal carbon is prepared, which solves the problems of high energy consumption and insufficient carbon sequestration capacity for invasive plants in the prior art, and realizes efficient carbon sequestration and green and low-carbon preparation process.
Patent Information
- Application Number
- CN202510096546.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art has problems such as high energy consumption and low efficiency when dealing with invasive plants, and there is little research on the carbon sequestration capacity of carbon materials, especially the research on improving carbon sequestration capacity by converting endogenous minerals into inorganic compounds has not been reported.
By immersing hollow lotus seed grass by FeCl3, the minerals contained in it are converted into FeC2O4, iron-impregnated hollow lotus seed grass hydrothermal carbon is prepared to improve its carbon sequestration ability.
The carbon sequestration capacity of hydrothermal carbon has been significantly increased, and the carbon retention rate has been increased to 73.48%. Invasive plants are used as raw materials to solve the problems of invasive plants flooding and carbon escape, and the preparation process is green and low-carbon.
Smart Images

Figure CN119797332A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of solid waste resource recycling and carbon sequestration, and specifically relates to a preparation method of iron-impregnated Alternanthera philoxeroides hydrothermal charcoal and application thereof in carbon sequestration. Technical Background
[0002] In response to the increasing global warming, my country has announced that its carbon dioxide emissions will peak before 2030. In order to achieve this goal, in addition to reducing carbon dioxide and fossil fuel emissions, negative emission technologies are also needed. One of the negative emission technologies is carbon sequestration, which is the process of capturing and storing atmospheric carbon dioxide. This technology aims to store and utilize residual carbon, create value-added products, and establish a balance between carbon dioxide emissions and atmospheric carbon offsets. In this context, converting solid waste biomass into carbon storage materials through hydrothermal carbonization (HTC) has become a promising and sustainable method.
[0003] The rapid spread of invasive plants poses a serious threat to global ecosystems and economic development. The existing common disposal methods for invasive plants have disadvantages such as high energy consumption and low efficiency. In order to achieve green and low-carbon development as soon as possible, it is urgent to find new technologies. As a typical invasive plant, Alternanthera philoxeroides has high biomass and rapid growth characteristics, which provide the possibility for sustainable utilization of raw materials. Using Alternanthera philoxeroides biomass as raw material to prepare hydrothermal charcoal can not only effectively reduce the number of invasive plants and reduce their harm to the ecosystem, but also make up for the shortcomings of common treatment methods, convert waste biomass into carbon sequestration materials, and achieve "using harm to control waste and turning harm into treasure".
[0004] Hydrochar is a solid product generated by wet biomass under high temperature and pressure. Its raw materials are widely available and low in cost. It has the characteristics of being porous, having a large specific surface area, having strong adsorption capacity, and having strong carbon stability. It has shown great potential in soil fertilization and greenhouse gas emission reduction, and has high ecological and economic benefits. The cellulose, hemicellulose, lignin, etc. in plant residues are converted into aromatic and highly polymerized stable carbon structures through HTC, so that 20% to 40% of the carbon in the biomass itself is fixed in the hydrochar for a long time. This is an effective carbon fixation pathway. Hydrochar can also increase the vegetation's ability to capture atmospheric CO2 by increasing the photosynthesis of aboveground vegetation and the biomass carbon pool, thereby increasing the negative emission potential of the soil ecosystem. Therefore, the research and application of carbon fixation in carbon materials has attracted widespread attention.
[0005] Publication No. CN 201510031274.1 A method for enhancing carbon fixation of biochar using phosphoric acid, wherein the biomass waste is crushed, then added with phosphoric acid aqueous solution, mixed and allowed to stand, and then heated to 400-600°C under nitrogen protection for pyrolysis reaction to obtain modified biochar. Compared with the biochar product without pretreatment, the carbon retention rate of the biochar increased from 46.8% to 63.9%.
[0006] XIAO R, WANG J , GASTON LA, et al. Biochar produced from mineralsalt-impregnated chicken manure: Fertility properties and potential for carbon sequestration [J]. Waste Management, 2018, 78: 802-10 discloses a biochar prepared by impregnating chicken manure with mineral salts, and investigates its fertility properties and carbon sequestration capacity. Chicken manure biomass impregnated with mineral salts (CaCl2, MgCl2·6H2O, FeCl3·6H2O) was pyrolyzed at 250℃-550℃ to obtain chicken manure biochar. In contrast, at 550℃, the modified biochar pretreated with mineral salts can reduce carbon loss by 15-20% during pyrolysis and has higher chemical and biological stability.
[0007] NAN H, ZHAO L, YANG F, et al. Different alkaline minerals interactedwith biomass carbon during pyrolysis: Which one improved biochar carbon sequestration[J]. Journal of Cleaner Production, 2020, 255 discloses a method for preparing biochar doped with cow dung with different alkaline minerals, and explores the effect of minerals on carbon sequestration by adding KCl, NaCl, MgCl2 and CaCl2 based on carbon retention before and after pyrolysis and carbon stability evaluated by K2Cr2O7 oxidation and biomineralization in real soil. When the mineral / biomass ratio was 1:5, the carbon retention rate in biochar could be increased from 49.8% (without minerals) to 52.5% (KCl), 53.7% (NaCl), 64.1% (MgCl2) and 60.7% (CaCl2).
[0008] NAN H, YIN J, YANG F, et al. Pyrolysis temperature-dependent carbon retention and stability of biochar with participation of calcium: Implications to carbon sequestration [J]. Environmental Pollution, 2021, 287 discloses a method for preparing biochar from cow dung doped with exogenous Ca, and explores the effect of different pyrolysis temperatures on the carbon sequestration rate of biochar under the doping of exogenous mineral Ca. Using cow dung as raw material, biochar was produced at 300℃, 400℃, 500℃ and 600℃. The addition of exogenous Ca increased the carbon retention rate in biochar by 16.6%, 23.4%, 29.1% and 31.1%, respectively.
[0009] LUO X, DU HY, DU J, et al. The influence of biomass type onhydrothermal carbonization: Role of calcium oxalate in enhancing carbonsequestration of hydrochar [J]. Journal of Environmental Management, 2024,349 discloses a preparation method for producing hydrochar from different types of invasive plants, and explores the influence of biomass type and endogenous minerals on the stability of hydrochar. A mixture of 4.5 g of different biomass raw materials and 40 mL of deionized water was placed in a 100 mL beaker and stirred vigorously for 15 min. The resulting suspension was transferred to a polytetrafluoroethylene-lined autoclave and then reacted in an oven at 150°C for 12 h. Among them, the thermal stability coefficient R of the hydrochar of Alternanthera philoxeroides was 1.347 W / cm2. 50 The value was 0.57, the carbon retention rate was 58.8%, and the formation of calcium oxalate during the HTC process improved the thermal and chemical stability of the hydrothermal carbon.
[0010] So far, all the research reports have been about improving the carbon sequestration capacity of carbon materials by adding exogenous minerals, while there are few studies on the effect of endogenous minerals on the carbon sequestration capacity of carbon materials. There are no reports on further exploring the effect of endogenous minerals on the carbon sequestration of carbon materials by converting them into inorganic compounds. Therefore, the present invention discloses a method for preparing iron-impregnated Alternanthera philoxeroides hydrothermal charcoal, which converts the minerals contained in Alternanthera philoxeroides into FeC2O4 by impregnating Alternanthera philoxeroides with FeCl3, thereby further improving the carbon sequestration capacity of the hydrothermal charcoal and providing a new method for the resource recycling of solid waste. Summary of the invention
[0011] The first object of the present invention is to provide a method for preparing iron-impregnated Alternanthera philoxeroides hydrothermal charcoal.
[0012] To achieve the first object of the present invention, a method for preparing iron-impregnated Alternanthera philoxeroides hydrothermal charcoal comprises the following steps: Cleaning the soil impurities on the surface of the collected Alternanthera philoxeroides, then drying it in an oven at 210° C., crushing it and sieving it to obtain Alternanthera philoxeroides powder; Dissolving Alternanthera philoxeroides powder and ferric chloride hexahydrate in deionized water to obtain a mixed solution A; The mixed solution A was stirred vigorously at room temperature (25°C), transferred to a polytetrafluoroethylene autoclave, reacted in an oven at 210°C, and centrifuged and washed to obtain iron-impregnated Alternanthera philoxeroides hydrothermal charcoal; Wherein, the ratio of ferric chloride hexahydrate, deionized water and raw materials is: 0.005~0.015 mol:40 mL:3.0~5.0 g.
[0013] In a specific embodiment, the particle size of the Alternanthera philoxeroides powder in step a is preferably 80-100 mesh.
[0014] In a specific embodiment, the concentration of ferric chloride hexahydrate in step b is 0.005 M to 0.0015 M, preferably 0.01 M.
[0015] In a specific embodiment, the mass of the Alternanthera philoxeroides powder in step b is 3.0-5.0 g, preferably 4.5 g.
[0016] In a specific embodiment, the reaction time of step c is 3-12 h, the stirring time at room temperature is 0.5-1 h, and after washing three times with pure water in a centrifuge at 6000-8000 rpm, it is dried at 80-100°C.
[0017] The second object of the present invention is to use the above-mentioned iron-impregnated Alternanthera philoxeroides hydrothermal charcoal in the field of carbon sequestration.
[0018] To achieve the second purpose of the present invention, the application of iron-impregnated Alternanthera philoxeroides hydrothermal charcoal in the field of carbon sequestration was evaluated by thermogravimetric analysis and H2O2 oxidation experiments for the thermal stability and antioxidant capacity of the hydrothermal charcoal.
[0019] In a specific embodiment, the temperature is increased continuously, the thermal analysis starts at 30°C and ends at 1000°C, and the heating rate is 10-20°C / min. By calculating the thermal stability coefficient (R 50 ) to evaluate the thermal stability of hydrothermal carbon.
[0020] In a specific embodiment, 0.5 g of hydrothermal carbon was added to a 50 mL test tube containing 40 mL of H2O2 (5%), and then the test tube was placed in a 60°C water bath for 48 h. The antioxidant capacity of hydrothermal carbon was measured by carbon retention rate (C R ) and the difference in C element content of hydrothermal char before and after H2O2 oxidation. Beneficial Effects
[0021] (1) The preparation method of the iron-impregnated Alternanthera philoxeroides hydrothermal charcoal of the present invention is simple, efficient, green, energy-saving, emission-reducing and low-cost.
[0022] (2) The iron-impregnated Alternanthera philoxeroides hydrothermal charcoal of the present invention utilizes the fact that Alternanthera philoxeroides itself contains rich mineral components, and introduces FeCl3 to convert it into FeC2O4, wherein the iron-impregnated Alternanthera philoxeroides hydrothermal charcoal R 50 The maximum value is 0.73, and the carbon retention rate C R is 73.48%. 50 is 0.57, and the carbon retention rate C R 58.8%), which significantly increases the carbon sequestration capacity of hydrothermal charcoal.
[0023] (3) The raw materials used in the iron-impregnated Alternanthera philoxeroides hydrothermal charcoal of the present invention are invasive plants, which solves the problems of invasive plant proliferation and carbon escape, and the preparation process is green and low-carbon. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 XRD diagrams of Examples 1-4 and Comparative Example 1, BC Fe -3. BC Fe -6.BC Fe -9. BC Fe -12 are embodiments 1, 2, 3 and 4.
[0025] Figure 2 FTIR images of Examples 1-4 and Comparative Example 1, BC Fe -3. BC Fe -6.BC Fe -9. BCFe -12 are embodiments 1, 2, 3 and 4.
[0026] Figure 3 The SEM images of Examples 1-5 and Comparative Example 1, BC Fe -3. BC Fe -6.BC Fe -9. BC Fe -12, BC Fe -24 are embodiments 1, 2, 3, 4, and 5.
[0027] Figure 4 is the TGA diagram of Examples 1-4 and Comparative Example 1, BC Fe -3. BC Fe -6.BC Fe -9. BC Fe -12 are embodiments 1, 2, 3 and 4.
[0028] Figure 5 The DTG diagrams of Examples 1-4 and Comparative Example 1, BC Fe -3. BC Fe -6.BC Fe -9. BC Fe -12 are embodiments 1, 2, 3 and 4.
[0029] Figure 6 H2O2-CRVs diagram of Examples 1-4 and Comparative Example 1, BC Fe -3. BC Fe -6.BC Fe -9. BC Fe -12 are embodiments 1, 2, 3 and 4. DETAILED DESCRIPTION
[0030] To achieve the first object of the present invention, a method for preparing iron-impregnated Alternanthera philoxeroides hydrothermal charcoal comprises the following steps: a. Clean the collected Alternanthera philoxeroides surface soil impurities, then dry in an oven at 210 ℃, crush and sieve to obtain Alternanthera philoxeroides powder; b. The Alternanthera philoxeroides powder and ferric chloride hexahydrate were dissolved in deionized water to obtain a mixture A; c. The mixed solution A was vigorously stirred at room temperature (25°C), transferred to a polytetrafluoroethylene-lined autoclave, reacted in an oven at 210°C, and centrifuged and washed to obtain iron-impregnated Alternanthera philoxeroides hydrothermal charcoal; Wherein, the ratio of ferric chloride hexahydrate, deionized water and raw materials is: 0.005~0.015 mol:40 mL:3.0~5.0 g.
[0031] In a specific embodiment, the particle size of the Alternanthera philoxeroides powder in step a is preferably 80-100 mesh.
[0032] In a specific embodiment, the concentration of ferric chloride hexahydrate in step b is 0.005 M to 0.0015 M, preferably 0.01 M.
[0033] In a specific embodiment, the mass of the Alternanthera philoxeroides powder in step b is 3.0-5.0 g, preferably 4.5 g.
[0034] In a specific embodiment, the reaction time of step c is 3-12 h, the stirring time at room temperature is 0.5-1 h, and after washing three times with pure water in a centrifuge at 6000-8000 rpm, it is dried at 80-100°C.
[0035] The second object of the present invention is to use the above-mentioned iron-impregnated Alternanthera philoxeroides hydrothermal charcoal in the field of carbon sequestration.
[0036] To achieve the second purpose of the present invention, the application of iron-impregnated Alternanthera philoxeroides hydrothermal charcoal in the field of carbon sequestration was evaluated by thermogravimetric analysis and H2O2 oxidation experiments for the thermal stability and antioxidant capacity of the hydrothermal charcoal.
[0037] In a specific embodiment, the temperature is increased continuously, the thermal analysis starts at 30°C and ends at 1000°C, and the heating rate is 10-20°C / min. By calculating the thermal stability coefficient (R 50 ) to evaluate the thermal stability of hydrothermal carbon.
[0038] ; Where T 50,hydrochar and T 50,graphite are the temperatures corresponding to 50% oxidation of hydrothermal carbon and graphite, respectively.
[0039] In a specific embodiment, 0.5 g of hydrothermal carbon was added to a 50 mL test tube containing 40 mL of H2O2 (5%), and then the test tube was placed in a 60°C water bath for 48 h. The antioxidant capacity of hydrothermal carbon was measured by carbon retention rate (C R ) and the initial carbon residue volumes (CRVs) after H2O2 oxidation treatment.
[0040] ; Where C hydrochar and C biomass are the C content of biochar and biomass (%); Y hybrochar is the biochar yield (%).
[0041] ; Where Br is the initial mass of the hydrothermal char before oxidation treatment, and BrC is the carbon content of the hydrothermal char; Br is the corresponding residual mass of the hydrothermal char after oxidation treatment, and BrC is the carbon content of the hydrothermal char.
[0042] The specific implementation modes of the present invention are further described below in conjunction with embodiments, but the present invention is not limited to the scope of the embodiments. Example
[0043] 40 mL of deionized water was added to a beaker containing 4.5 g of Alternanthera philoxeroides powder and 0.01 mol FeCl3·6H2O. The mixture was then vigorously stirred at room temperature (25°C) for 1 h. The mixture was then transferred to a 100 mL polytetrafluoroethylene autoclave and placed in an oven at 210°C for 3 h. After the reaction was completed, the supernatant was discarded after cooling. The remaining material was washed three times with deionized water, and the solution was placed in an oven at 100°C for drying for 24 h to obtain iron-impregnated Alternanthera philoxeroides hydrothermal charcoal (BC). Fe -3). Example
[0044] 40 mL of deionized water was added to a beaker containing 4.5 g of Alternanthera philoxeroides powder and 0.01 mol FeCl3·6H2O. The mixture was then vigorously stirred at room temperature (25°C) for 1 h. The mixture was then transferred to a 100 mL polytetrafluoroethylene autoclave and placed in an oven at 210°C for 6 h. After the reaction was completed, the supernatant was discarded after cooling. The remaining material was washed three times with deionized water, and the solution was placed in an oven at 100°C for drying for 24 h to obtain iron-impregnated Alternanthera philoxeroides hydrothermal charcoal (BC). Fe -6), carbon retention rate (C R ) is calculated to be 73.48%. Example
[0045] 40 mL of deionized water was added to a beaker containing 4.5 g of Alternanthera philoxeroides powder and 0.01 mol FeCl3·6H2O. The mixture was then vigorously stirred at room temperature (25°C) for 1 h. The mixture was then transferred to a 100 mL polytetrafluoroethylene autoclave and placed in an oven at 210°C for 9 h. After the reaction was completed, the supernatant was discarded after cooling. The remaining material was washed three times with deionized water, and the solution was placed in an oven at 100°C for drying for 24 h to obtain iron-impregnated Alternanthera philoxeroides hydrothermal charcoal (BC). Fe -9). Example
[0046] 40 mL of deionized water was added to a beaker containing 4.5 g of Alternanthera philoxeroides powder and 0.01 mol FeCl3·6H2O. The mixture was then vigorously stirred at room temperature (25°C) for 1 h. The mixture was then transferred to a 100 mL polytetrafluoroethylene autoclave and placed in an oven at 210°C for 12 h. After the reaction was completed, the supernatant was discarded after cooling. The remaining material was washed three times with deionized water, and the solution was placed in an oven at 100°C for 24 h to obtain iron-impregnated Alternanthera philoxeroides hydrothermal charcoal (BC). Fe -12). Example
[0047] 40 mL of deionized water was added to a beaker containing 4.5 g of Alternanthera philoxeroides powder and 0.01 mol FeCl3·6H2O. The mixture was then vigorously stirred at room temperature (25°C) for 1 h. The mixture was then transferred to a 100 mL polytetrafluoroethylene autoclave and placed in an oven at 210°C for 24 h. After the reaction was completed, the supernatant was discarded after cooling. The remaining material was washed three times with deionized water, and the solution was placed in an oven at 100°C for 24 h to obtain iron-impregnated Alternanthera philoxeroides hydrothermal charcoal (BC). Fe -twenty four).
[0048] Hydrothermal carbonization of raw Alternanthera philoxeroides: 4.5 g of Alternanthera philoxeroides powder and 40 mL of deionized water were mixed and then vigorously stirred for 15 min. The resulting suspension was placed in a 100 mL polytetrafluoroethylene autoclave and kept in an oven at 210 °C for 12 h to obtain Alternanthera philoxeroides hydrothermal carbon (BAP). The carbon retention rate (C R ) is calculated as 58.8%.
[0049] Figure 1 Figure 2 shows the XRD patterns of hydrothermal carbon of Alternanthera philoxeroides impregnated with iron for different time periods. The XRD spectrum shows the characteristic peak of ferrous oxalate (PDF#23-0293), while the characteristic peak of calcium oxalate (PDF#20-0231) disappears, indicating that a new iron salt mineral FeC2O4 is formed after ferric chloride impregnation.
[0050] Figure 2 The FTIR images of hydrothermal charcoal of Alternanthera philoxeroides impregnated with iron for different times show that more functional groups were added to the charcoal surface after ferric chloride impregnation, and the stretching vibration of Ca-O was transformed into the stretching vibration of Fe-O.
[0051] Figure 3 These are the SEM images of hydrothermal charcoals of Alternanthera philoxeroides impregnated with iron at different times. It was found that compared with the original hydrothermal charcoal of Alternanthera philoxeroides, the skeleton structure of the hydrothermal charcoal of Alternanthera philoxeroides impregnated with iron was more perfect, and spherical particles of FeC2O4 were generated on the surface and around the hydrothermal charcoal.
[0052] Figure 4 The TGA diagrams of hydrothermal charcoal of Alternanthera philoxeroides impregnated with iron for different times further visualize the thermal decomposition process of Alternanthera philoxeroides. It was found that the hydrothermal charcoal had three different degrees of weight loss rate.
[0053] Figure 5 The DTG graphs of hydrothermal charcoal of Alternanthera philoxeroides impregnated with iron for different times. The second DTG peak of the hydrothermal charcoal of Alternanthera philoxeroides impregnated with iron at 400°C red-shifted to 450°C relative to the DTG peak of the original hydrothermal charcoal, indicating that the formation of FeC2O4 improves the activation energy and thermal stability of the hydrothermal charcoal.
[0054] Figure 6 For BAP, BC Fe -3 and BC Fe -6 H2O2-CRVs graph, it can be found that the iron-impregnated Alternanthera philoxeroides hydrothermal carbon (BC Fe -3 and BC Fe -6) was 26.61% higher than that of BAP. The higher the CRVs, the stronger the antioxidant capacity, chemical stability and carbon sequestration capacity of the biochar.
Claims
1. A method for preparing iron-impregnated Alternanthera philoxeroides hydrothermal charcoal, characterized in that: The method comprises: a. Clean the collected Alternanthera philoxeroides surface soil impurities, then dry in an oven at 210 ℃, crush and sieve to obtain Alternanthera philoxeroides powder; b. The Alternanthera philoxeroides powder and ferric chloride hexahydrate were dissolved in deionized water to obtain a mixture A; c. The mixed solution A was vigorously stirred at room temperature (25°C), transferred to a polytetrafluoroethylene autoclave, reacted in an oven at 210°C, and centrifuged and washed to obtain iron-impregnated Alternanthera philoxeroides hydrothermal charcoal; Wherein, the ratio of ferric chloride hexahydrate, deionized water and raw materials is: 0.005~0.015 mol:40 mL:3.0~5.0 g.
2. The method for preparing iron-impregnated Alternanthera philoxeroides hydrothermal charcoal according to claim 1, characterized in that: The particle size of the Alternanthera philoxeroides powder in step a is preferably 80-100 mesh.
3. The method for preparing iron-impregnated Alternanthera philoxeroides hydrothermal charcoal according to claim 1, characterized in that: The concentration of ferric chloride hexahydrate in step b is 0.005 mol ~ 0.0015 mol, preferably 0.01 mol.
4. The method for preparing iron-impregnated Alternanthera philoxeroides hydrothermal charcoal according to claim 1, characterized in that: The mass of the Alternanthera philoxeroides powder in step b is 3.0-5.0 g, preferably 4.5 g.
5. The method for preparing iron-impregnated Alternanthera philoxeroides hydrothermal charcoal according to claim 1, characterized in that: In a specific embodiment, the reaction time of step c is 3-12 h, the stirring time at room temperature is 0.5-1 h, and after washing three times with pure water in a centrifuge at 6000-8000 rpm, it is dried at 80-100°C.
6. Application of the iron-impregnated Alternanthera philoxeroides hydrothermal charcoal prepared by the method according to any one of claims 1 to 5 in the field of carbon sequestration, characterized in that: The thermal stability and antioxidant capacity of the hydrothermal carbon were evaluated by thermogravimetric analysis and H2O2 oxidation experiments.
7. The use according to claim 6, characterized in that: The heating is continuous, the thermal analysis starts at 30°C and ends at 1000°C, and the heating rate is 10-20°C / min. 50 ) to evaluate the thermal stability of hydrothermal charcoal.
8. The use according to claim 6, characterized in that: 0.5 g of hydrochar was added to a 50 mL test tube containing 40 mL of H2O2 (5%), and then the test tube was placed in a 60°C water bath for 48 h. The antioxidant capacity of hydrochar was measured by carbon retention rate (C R ) and the difference in C element content of hydrothermal char before and after H2O2 oxidation.
Citation Information
Patent Citations
A method for strengthening carbon sequestration by biochar using phosphoric acid
CN104673338B